2011
DOI: 10.1126/science.1208049
|View full text |Cite
|
Sign up to set email alerts
|

Npas4 Regulates a Transcriptional Program in CA3 Required for Contextual Memory Formation

Abstract: The rapid encoding of contextual memory requires the CA3 region of hippocampus, but the necessary genetic pathways remain unclear. We found that the activity-dependent transcription factor Npas4 regulates a transcriptional program in CA3 that is required for contextual memory formation. Npas4 was specifically expressed in CA3 after contextual learning. Global knockout or selective deletion of Npas4 in CA3 both resulted in impaired contextual memory, and restoration of Npas4 in CA3 was sufficient to reverse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
295
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(323 citation statements)
references
References 53 publications
20
295
1
1
Order By: Relevance
“…during memory consolidation (31), which is consistent with a role of this circuit in associating contextual cues with aversive events (11,12). Based on these results, we suggest that CRTC1 participates in transcriptional events mediating contextual memory in the dorsal hippocampus, a region required for contextual memory encoding (15,54).…”
Section: Discussionsupporting
confidence: 62%
“…during memory consolidation (31), which is consistent with a role of this circuit in associating contextual cues with aversive events (11,12). Based on these results, we suggest that CRTC1 participates in transcriptional events mediating contextual memory in the dorsal hippocampus, a region required for contextual memory encoding (15,54).…”
Section: Discussionsupporting
confidence: 62%
“…In our study, a ChIP assay showed that Npas4 binds the promoter of NeuN in Neuro2a cells. Accordingly, NPAS4 may have indirect effects through the regulation of other transcriptional factors (18). Taking these findings together, it is suggested that NPAS4 contributes to neurite development and functional maturation of neurons through the transcriptional regulation of neurotransmission and neurodevelopment-associated molecules.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study demonstrated that the activity-dependent expression of NPAS4 regulates a transcriptional program in the CA3 hippocampus required for contextual memory formation (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, IEG induction mediates the plasticity underlying complex processes such as learning, memory, and behavior (6)(7)(8). Thus, genetic deletion of these IEGs often leads to deficits in the encoding and consolidation of longterm memory (9)(10)(11). Signaling cascades in which neural activity induces IEGs have been elusive.…”
mentioning
confidence: 99%